Central control of energy metabolism and hypothalamic obesity - (:unkn) unknown (Humana Press Inc., 2018)
Energy balance in humans is regulated by a complex neuroendocrine system centered in the hypothalamus. The mechanical or functional disruption of the hypothalamic network that regulates energy homeostasis causes intractable weight gain, which is termed "hypothalamic obesity (HyOb)." It took many years to discover mechanisms by which the hypothalamus controls energy homeostasis, but recent studies have clarified how the hypothalamus regulates appetite and satiety. The disruptions causing HyOb can result from brain tumors, neurosurgery, cranial radiotherapy, and genetic defects. Unfortunately, attempts at controlling HyOb through diet, exercise, or pharmacological treatment are not satisfactory at the moment. However, new treatment opportunities in genetic forms of obesity and the application of bariatric surgery hold promise for the treatment of HyOb. This chapter summarizes hypothalamic appetite regulation and the pathophysiology, metabolic features, etiology, clinical characteristics, and treatment modalities for hypothalamic obesity in children and adolescents. © Springer International Publishing AG 2018.
Keywords: Arcuate nucleus; Bariatric surgery; Craniopharyngioma; Hyperleptinemia; Hyperphagia; Hypothalamic obesity